Substituted Aminoacetamides as Novel Leads for Malaria Treatment. (3rd July 2019) - Norcross, Neil R.; Wilson, Caroline; Baragaña, Beatriz; Hallyburton, Irene; Osuna‐Cabello, Maria; Norval, Suzanne; Riley, Jennifer; Fletcher, Daniel; Sinden, Robert; Delves, Michael; Ruecker, Andrea; Duffy, Sandra; et al.
Abstract: Herein we describe the optimization of a phenotypic hit against Plasmodium falciparum based on an aminoacetamide scaffold. This led to N ‐(3‐chloro‐4‐fluorophenyl)‐2‐methyl‐2‐[4‐methyl‐3‐(morpholinosulfonyl)phenyl]aminopropanamide (compound 28 ) with low‐nanomolar activity against the intraerythrocytic stages of the malaria parasite, and which was found to be inactive in a mammalian cell counter‐screen up to 25 μm . Inhibition of gametes in the dual gamete activation assay suggests that this family of compounds may also have transmission blocking capabilities. Whilst we were unable to optimize the aqueous solubility and microsomal stability to a point at which the aminoacetamides would be suitable for in vivo pharmacokinetic and efficacy studies, compound 28 displayed excellent antimalarial potency and selectivity; it could therefore serve as a suitable chemical tool for drug target identification. Abstract : New roads to novel chemotypes : Compound selection from the TCAMS library (GSK), followed by iterative rounds of inhibitor design and synthesis afforded a single‐digit nanomolar inhibitor of P. falciparum (3D7), based on an aminoacetamide core. Compound 28 is a potent antimalarial and displayed excellent selectivity in a mammalian counter‐screen. This compound could be used as a suitable chemical tool for drug target identification or as a lead compound for further optimization.